2015
DOI: 10.3390/w7084385
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Dimension of Cohesive Sediment Flocs at Steady State under Seven Shear Flow Conditions

Abstract: Abstract:The morphological properties of kaolin flocs were investigated in a Couette-flow experiment at the steady state under seven shear flow conditions (shear rates of 5.36, 9.17, 14, 24, 31, 41 and 53 s −1 ). These properties include a one-dimensional (1-D) fractal dimension (D1), a two-dimensional (2-D) fractal dimension (D2), a perimeter-based fractal dimension (Dpf) and an aspect ratio (AR). They were calculated based on the projected area (A), equivalent size, perimeter (P) and length (L) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Suspended sediments containing flocks have higher settling velocities compared to individual particles; hence, they can settle and be deposited faster in regions with lower turbulent energies. The observed results were in line with the findings of previous studies conducted by Pejrup and Zhu et al [37,38]. As current speeds and wave heights were reduced, the amount of sediment deposited increases in the landward area behind the breakwater, thus, the sediment accumulations were also higher during the NE season.…”
Section: Sediment Transport and Erosion-deposition Pattern During Thesupporting
confidence: 92%
See 1 more Smart Citation
“…Suspended sediments containing flocks have higher settling velocities compared to individual particles; hence, they can settle and be deposited faster in regions with lower turbulent energies. The observed results were in line with the findings of previous studies conducted by Pejrup and Zhu et al [37,38]. As current speeds and wave heights were reduced, the amount of sediment deposited increases in the landward area behind the breakwater, thus, the sediment accumulations were also higher during the NE season.…”
Section: Sediment Transport and Erosion-deposition Pattern During Thesupporting
confidence: 92%
“…Previous research has reported that cohesive sediments have low settling velocities and therefore could be transported over a long distance before settling through water column [36][37][38]. However, the cohesive behaviour of fine sediments allow them to agglomerate and form bigger-sized aggregates called flocks, with higher settling velocities compared to single-particle fine sediments.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some fragile and loose flocs may break into small flocs and/or primary particles (floc breakage or floc disaggregation) due to the flow shear [3][4][5]. Flocs are totally different from primary sediment particles in terms of their larger sizes, lower excess density, and higher settling velocity in water [2,6]. Studying cohesive sediment flocculation in a turbulent flow environment is essential because it plays an important role in affecting the morphological changes to coastal areas, dredging operations in navigational canals, and sediment siltation in reservoirs and 2 of 20 lakes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The c is the floc strength, which strongly depends on the method used to measure the floc size, while the γ is the stable floc size exponent depending on the breakage mechanisms (erosion or fracture) for flocs smaller or larger than the smallest eddy (i.e., Kolmogorov microscale) in the turbulent flow [28,29]. Some studies have focused on the structural and morphological properties of the flocs at the steady state of flocculation with respect to various flow shear conditions (e.g., References [6,17,25,30]). For example, Stone and Krishnappan [30] showed that particle boundaries become more convoluted and the shape of larger particles are more irregular at higher levels of flow shear stress, whereas Zhu et al [6] reported that with increasing flow shear rates, the flocs become less elongated and their boundary lines become tighter and more regular.…”
Section: Introductionmentioning
confidence: 99%
“…In natural estuarine waters turbulence varies during the tidal cycle (Zhu et al 2015). This specific scenario was explored in this as the effect of turbulence on FSD over time.…”
Section: Effect Of Turbulence Change Over Time On Fsdmentioning
confidence: 99%